Time almanac, 2008 (Chicago, 2008)
A compendium of facts, statistics, dates, and other information for the year 2007, noting significant news stories and people and covering topics in over forty alphabetized categories from astronomy to writing and language. Includes a photographic review of the year
Keywords: Almanacs